A New Species of Megastigmus and First Record of the Genus and Megastigmidae Family from the Paradise of the Maldives Archipelago - Irinel Eugen Popescu; Irina Neta Gostin (Insects, 2023)
Megastigmidae comprises more than 200 species in 12 genera. Megastigmus has a worldwide distribution with more than 150 species. Over 80% of these species are recorded from the Australian and Palearctic region, with a few from Afrotropical and Oriental regions, but none from the Neotropical region. We describe a new species of Megastigmus obtained from the seeds of Pemphis acidula in the Maldives Archipelago. This is the first mention of Megastigmidae having as a host plant a species from Lythraceae. It is also the first recorded association of Chalcidoidea with the genus Pemphis and the first mention of Megastigmidae and Megastigmus in the Maldives Archipelago. We provide a detailed description of the species, focusing on its morphology, using both light microscopy and scanning electron microscopy (SEM). Megastigmus irinae Popescu n. sp. is a strictly phytophagous species, with each larva consuming a single seed. Currently, M. irinae is an endemic species found only in the Maldives Archipelago. However, considering the distribution of its host plant, P. acidula, which ranges from East Africa to Southeast Asia, Australia, Micronesia, and French Polynesia, we anticipate that future research could significantly expand the known range of this interesting new species.